672 Diffusion Basis Spectrum Imaging Provides Insights into Cervical Spondylotic Myelopathy Pathology. (April 2023) - Zhang, Justin; Javeed, Saad; Greenberg, Jacob K.; Jayasekera, Dinal; Song, Chunyu; Dibble, Christopher; Blum, Jacob; Sun, Peng; Song, Sheng-Kwei; Ray, Wilson Zachary
Abstract : INTRODUCTION: Diffusion basis spectrum imaging (DBSI) is a non-invasive quantitative imaging modality that may improve understanding of cervical spondylotic myelopathy (CSM) pathology through detailed evaluations of spinal cord microstructural compartments. METHODS: A single-center prospective cohort study enrolled fifty CSM patients and twenty controls from 2018-2020. All patients underwent clinical evaluation and diffusion-weighted MRI, followed by diffusion tensor imaging (DTI) and DBSI analyses. Diffusion-weighted MRI metrics assessed white matter integrity by fractional anisotropy, axial diffusivity, radial diffusivity, and fiber fraction. In addition, DBSI further evaluates extra-axonal changes by isotropic restricted and non-restricted fraction. Including an intra-axonal diffusion compartment, DBSI improves estimations of axonal injury via intra-axonal axial diffusivity. Patients were categorized into mild, moderate, and severe CSM using mJOA classifications. Imaging parameters were compared among patient groups using independent-samples t-tests and ANOVA. RESULTS: Twenty controls, 27 mild (mJOA 15-17), 12 moderate (12-14) and 11 severe (0-11) CSM patients were enrolled. All patient-reported outcome measures were worse in CSM patients (all p < 0.001). DTI and DBSI fractional anisotropy, axial diffusivity, and radial diffusivity were significantly different between control and CSM patients (p < 0.05). DBSI fiber fraction, restricted fraction, and non-restricted fraction were significantly different between groups (p < 0.01). DBSI intra-axonal axial diffusivity was lower in mild compared to moderate (mean difference [95% CI]: 1.1 [0.3, 2.1], p < 0.01) and severe (1.9 [1.3, 2.4], p < 0.001) CSM. CONCLUSIONS: DBSI offers granular data on white matter tract integrity in CSM that provide novel insights into disease pathology, supporting its potential utility as a biomarker of CSM disease progression.